RECORDING THE CALCIUM SPECTRUM IN CAPILLARY LAMP - Bondarenko, Yu. N.; Scheglov, P. V. (Одеські астрономічні публікації, 2017)
Considered possibility of fabrication in laboratory conditions of special tubes with metals vapours of increased brightness. Shown possibility of their use for astronomical instruments.